Two Regions of the Human Platelet F11-Receptor (F11R) Are Critical for Platelet Aggregation, Potentiation and Adhesion - Babinska, Anna; Kedees, Mamdouh H.; Athar, Humra; Sobocki, Tomasz; Sobocka, Malgorzata B.; Ahmed, Tahir; Ehrlich, Yigal H.; Hussain, M. Mahmood; Kornecki, Elizabeth (Thrombosis and Haemostasis, 2002)
The F11 receptor (F11R) was first identified on the surface of human platelets as a target for a stimulatory monoclonal antibody (M.Ab.F11) that induces secretion, followed by exposure of fibrinogen receptors and aggregation. Cloning of the gene of F11R has revealed that this protein is a cell adhesion molecule (CAM), a member of the Ig superfamily and an ortholog of the murine protein called junctional adhesion molecule (JAM). The present study has identified two domains through which M.Ab.F11 triggers a platelet response culminating with aggregation. M.Ab.F11-mediated platelet adhesion, and the potentiation of collagen and ADP-induced platelet aggregation by M.Ab.F11, were found to involve the same two domains. A F11R recombinant protein (sF11R) completely inhibited platelet aggregation, adhesion and potentiation induced by M.Ab.F11, indicative that the active conformation of the external domain of F11R is present in the soluble, secreted recombinant protein. Furthermore, a specific peptide containing the sequence of the N-terminal amino acids S-1 to C-23 of F11R, and a peptide with the sequence of K-70 to C-82 in the 1st immunoglobulin-like (Ig) fold of F11R, both inhibited M.Ab.F11-induced aggregation, adhesion and potentiation of the aggregation of human platelets. Modeling of the 3D structure of the extracellular domain of the human platelet F11R suggests that these two regions form an active site within the conformation of this CAM. The sequence of these functional domains of F11R (in the N-terminus and 1st Ig-fold) provide the basis for new drug development in the treatment of certain types of thrombocytopenia and inflammatory thrombosis.
Keywords: Human platelet F11 receptor; F11R; junctional adhesion molecule; JAM